3-Aminobenzamide Blocks MAMP-Induced Callose Deposition Independently of Its Poly(ADPribosyl)ation Inhibiting Activity - Keppler, Brian D.; Song, Junqi; Nyman, Jackson; Voigt, Christian A.; Bent, Andrew F. (Frontiers in Plant Science, 2018)
Cell wall reinforcement with callose is a frequent plant response to infection. Poly(ADP-ribosyl)ation is a protein post-translational modification mediated by poly(ADP-ribose) polymerases (PARPs). Poly(ADP-ribosyl)ation has well-known roles in DNA damage repair and has more recently been shown to contribute to plant immune responses. 3-aminobenzamide (3AB) is an established PARP inhibitor and it blocks the callose deposition elicited by flg22 or elf18, two microbe-associated molecular patterns (MAMPs). However, we report that an Arabidopsis parp1parp2parp3 triple mutant does not exhibit loss of flg22-induced callose deposition. Additionally, the more specific PARP inhibitors PJ-34 and INH2BP inhibit PARP activity in Arabidopsis but do not block MAMP-induced callose deposition. These data demonstrate off-target activity of 3AB and indicate that 3AB inhibits callose deposition through a mechanism other than poly(ADP-ribosyl)ation. POWDERY MILDEW RESISTANT 4 (PMR4) is the callose synthase responsible for the majority of MAMP- and wound-induced callose deposition in Arabidopsis. 3AB does not block wound-induced callose deposition, and 3AB does not reduce the PMR4 mRNA abundance increase in response to flg22. Levels of PMR4-HA protein increase in response to flg22, and increase even more in flg22 + 3AB despite no callose being produced. The callose synthase inhibitor 2-deoxy-D-glucose does not cause similar impacts on PMR4-HA protein levels. Beyond MAMPs, we find that 3AB also reduces callose deposition induced by powdery mildew (Golovinomyces cichoracearum) and impairs the penetration resistance of a PMR4 overexpression line. 3AB thus reveals pathogenesis-associated pathways that activate callose synthase enzymatic activity distinct from those that elevate PMR4 mRNA and protein abundance.